Drug Prescribing Pattern among the Inpatients in the Surgery Department of Tertiary Hospital of Eastern Nepal - Panday, Dipesh Raj; Rauniar, Gajendra Prasad; Rai, Dillisher; Shah, Rupesh; Pandey, Karishma Rajbhandari (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: Prescription is a written instruction by a health care personnel to pharmacist to dispense drug(s). Irrational drug prescribing is a global problem, particularly in developing and transitional countries. This study was conducted to see the status of World Health Organization (WHO) core prescription indicators, complementary indices and prescription errors. Methods: It was a quantitative cross-sectional descriptive study carried out among inpatients of general surgery of tertiary hospital in eastern Nepal. Ethical approval for the study was obtained from the Institutional Review Committee. It was a convenience sampling. Calculated Sample size was 224. Enrollment of patients started on 16 May 2018 with the last case being enrolled on 1 Oct 2019 after obtaining informed consent. Relevant data was entered in a semi-structured proforma. Microsoft excel 2016 and IBM Statistical Package for the Social Sciences (SPSS) v. 21 were used for descriptive statistics. Results: Median age of inpatients was 40 (24 - 54) years with male: female ratio being 1.05. Total 1492 drugs were prescribed in 224 prescriptions. Mean number of drugs prescribed was 6.66 ± 2.33. Percentage of drugs prescribed by generic name was 25.60%. Prescriptions with at least one antimicrobial agent was 89.3%. Prescriptions with at least one injection was 92.9%. Percentage of drugs prescribed from the WHO Essential Medicine List was 66.48%. Other complementary prescribing indicators and prescription errors were also calculated. Conclusions: Most prescription indicators were inadvertently deviated away from WHO standards. Prescription errors were comparable to other studies.